PERKEMBANGAN KEJIWAAN MUSA DALAM NOVEL MADIELIEF KARYA KIRANADA: KAJIAN TEORI PSIKODINAMIKA SIGMUND FREUD - Rahmadani, Hanikmah; Tjahjono, Tengsoe (TRANSFORMATIKA, 2023)
Novels are never separated from psychological values because the problems told in novels are always related to the psychology of the characters created by the author. This psychological aspect is usually displayed through the character traits and behavior of the characters that are a problem as experienced by humans in real life. Like the novel Madielief by Kiranada which tells the psychological problems of the characters in it. Therefore, this research is examined using psychodynamic theory which aims to describe the psychological development of characters according to Sigmund Freud. This type of research is qualitative research with a literary psychology approach. The data were obtained from the novel Madielief by Kiranada. Research data are in the form of words, phrases, and sentences in paragraphs related to the problem statement. Data collection techniques using reading and note techniques. The results of this study indicate 1) Musa’s personality background in Kiranada’s Madielief novel, 2) Musa’s neurotic form of anxiety in Kiranada’s Madielief novel, 3) The psychological development of Musa in the Canadian Madielief novel